UJI PEFORMA RANCANG BANGUN PORTABLE VACUUM GRAIN CONVEYOR TIPE CENTRIFUGAL FAN - Dedi Suwandi; Tito Endramawan; Adi Suheryadi; Alfarisi Alfarisi; Felix Dionisius (P3M Politeknik Negeri Indramayu, 2022)
Portable vacuum grain conveyor (PVGC) work as transporting grain materials such as grain, wheat, sorghum, corn and its kind using air media. The advantages of this machine are that it can move material quickly, the material does not fall in the transportation process, it can move from the bottom to the top or vice versa, it does not require a feed hopper, and the machine can move places. How the PVGC machine works by utilizing the suction and thrust of a vacuum blower. The seed material is sucked in by the input hose and then into the cyclone to separate the air and seed material. Air from the cyclone enters the vacuum blower through the input hole and is blown into the output line to push the material falling from the cyclone through the rotary airlock. Seed material out through the output hose is directed to the desired place. Performance testing of the PVGC engine includes noise, the air suction speed of the input hose and the thrust speed of the output hose, the engine capacity, and thermal testing. The highest noise test results in the electric vacuum blower motor was 95.5 dBA ±1, the air suction speed at the input hose was 38 m/s ±3, the air thrust speed at the output hose was 44 m/s ±2, the capacity of the PVGC machine could transport IR64 of grain type with weighing 88 kg/minute. The hottest component was in the vacuum blower with a temperature of 52.50C.